Big-M Based MIQP Method for Economic Dispatch With Disjoint Prohibited Zones - Ding, Tao; Bo, Rui; Gu, Wei; Sun, Hongbin (IEEE transactions on power systems, 2014)
This paper presents a novel big-M based mixed integer quadratic programming (MIQP) method to solve economic load dispatch problem with disjoint prohibited zones. By adding artificial 0-1 binary variables for each prohibited operating zone of generators and employing a binary coding scheme, disjoint feasible regions are represented by complementary linear constraints. Compared to existing MIQP method, the proposed method can achieve global optimal solution with much reduced problem complexity.